Peningkatan Keterampilan Sholat Dalam Proses Pembelajaran Dengan Menggunakan Video Animasi - Ach Khusnan (LPPM STAI Al-Azhar Menganti Gresik, 2022)
Learning to pray is a challenge for students to awaken their spiritual attitude and ability to pray properly. And the media used in learning should use multimedia-based media, this is in line with the characteristics of the 2013 curriculum listed in the annex to Permendikbud number 67 of 2013 concerning the Basic Framework and Structure of the 2013 Curriculum SD/MI. Through multimedia-based media, the experience that students receive is not only through text, but also audio and visual. In light of this background, the researcher wanted to know the ability of students in learning to pray and how to apply animated video media in improving students' prayer skills in Class III MI Tarbiyatul Muta'allimin Wonokoyo Menganti Gresik. To find out this, the researcher uses a type of animated video media in learning PAI in the prayer chapter. And the results of this study show that before the application of animated video media, the ability of class II students in the fiqh learning competency in prayer chapter material was still lacking, of all class II students only 30% of students who successfully passed the Pre-Cycle. 70% percent are declared not passed because the average value does not meet the SKM. And animated video media is said to be successfully applied in learning Fiqh Materials in the Prayer chapter with a value of > 75. This value is obtained from the observation sheet of the accompanying teacher with a score of 77.5. Animated video media is said to be effective in learning Fiqh Materials in the Prayer chapter for second grade students with an average percentage of 98.2%. In attitude competence, the minimum score achieved by students is B (good). The maximum value achieved is SB (very good). In the knowledge competence, in cycle I 50% percent of the 32 students managed to get the KKM standard with a minimum score of 75.00 and a maximum score of 95.00. Whereas in cycle II there was an increase of 14% percent from the previous stage which was initially 50% to 64%, with the maximum score achieved being 100. In skills competence, the maximum score achieved by students was 91.67. There were 3 students who scored 66.67 which were categorized under the KKM, here the researcher had tried to do remedial for the 2 students so that their scores reached the KKM. At this last stage 91.4% of students said And 8% of participants had not been said to be complete because the results achieved did not meet the minimum standard of completeness criteria (SKKM).